O policiamento comunitário na Polícia Civil de Minas Gerais: um estudo sobre mudança organizacional - Daniel Araujo de Azevedo (2017)
The purpose of this paper is to understand how the community policing model is inserted in the Civil Police of Minas Gerais and to what extent this model promotes a true organizational change. Alternatively, I problematize the fact that if, instead of promoting organizational change, community policing is just a new name for old practices within the Civil Police of Minas Gerais. Thus, this dissertation presents the mapping of the community policing model, through the teaching projects and strategies of police action based on this philosophy within the PCMG, seen as a process of organizational change that can be explained by the theories of economic sociology and sociology of organizations.